Analisis Potensi Minyak Jelantah Sebagai Bahan Baku Produksi Biodiesel di Kota Pekanbaru : Analisis Potensi Minyak Jelantah Sebagai Bahan Baku Produksi Biodiesel di Kota Pekanbaru - Nanda Putri Miefthawati; Tegar Setiadi, Rexy (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2023)
Fuel Oil is a basic need for society, with a consumption rate of 42% in Indonesia. The high level of consumption, especially for diesel fuel, with supplies and availability of raw materials dwindling makes scarcity a common phenomenon in urban areas. Alternative innovations in the supply of raw materials need to be carried out, one of which is by using alternative raw materials in the form of Biodiesel derived from urban waste cooking oil. The aim of this research is to utilize the 40,000 Kg/month waste of used cooking oil in Pekanbaru City to be converted into Biodiesel with the Transesterification Method in the form of a chemical reaction Fat reacted with methanol and catalyst with the help of Superpro Design software is capable of producing a volume of biodiesel of 33,407 liters per month, a fuel density of 866/km3 with a production cost of IDR 6,000/liter and a selling price of IDR 11,000 per liter which has the potential to make biodiesel an alternative to diesel for the people of Pekanbaru City.